Kidney transplantation in a patient with familial mediterranean fever complicated by secondary amyloidosis (clinical report) - K. G. Tayler; Sh. R. Galeev (Вестник трансплантологии и искусственных органов)
The paper presents a clinical case of successful kidney transplantation (KTx) in a patient with end-stage chronic kidney disease (ESKD) resulting from familial Mediterranean fever (FMF). Pre-transplant preparation and posttransplant management tactics are presented. The authors conclude that ESKD can be effectively treated by KTx in a patient with FMF against the background of ongoing pathogenetic therapy in autoinflammation.